Childhood Maltreatment Is Associated with Ulcerative Colitis but Not Crohn's Disease: Findings from a Population-based Study. Issue 11 (November 2015) - Fuller-Thomson, Esme; West, Keri J.; Sulman, Joanne; Baird, Stephanie L.
Abstract : Background: Previous research suggests a link between childhood adversities and inflammatory bowel disease (IBD); however, study limitations prevent generalization of findings. To address this, the current study uses a Canadian population–based sample to investigate the relationship between 3 childhood adversities and 2 types of IBD while controlling for a range of factors. Methods: Secondary data analysis of a subsample of the nationally representative 2012 Canadian Community Health Survey—Mental Health consisted of those with no missing data on any of the variables of interest (n = 21, 852). The survey response rate was 68.9%. This study used logistic regression to estimate odds ratios of 3 types of childhood adversities (physical abuse, sexual abuse, and witnessing parental domestic violence) separately for ulcerative colitis and Crohn's disease, each compared with those without IBD. The final model controls for sociodemographics, health behaviors, and mental health. The exposure was assessed by retrospective self-report, and the outcome was by self-report of a health professional diagnosis. Results: In a fully adjusted model, those who are physically (odds ratio = 2.28; confidence interval, 1.39–3.75) or sexually abused (odds ratio = 2.64; confidence interval, 1.61–4.33) during childhood had significantly higher odds of ulcerative colitis than their non-maltreated peers. No relationship is found between witnessing parental domestic violence and ulcerative colitis. None of the early adversities are significantly related to Crohn's disease. Conclusions: Childhood physical and sexual abuse are related to ulcerative colitis, but not Crohn's disease. Future research that can address epigenetic and neuroendocrine factors should investigate pathways through which early adversities may translate into one type of IBD but not another. Abstract : Article first published online 30 July 2015.